2010
DOI: 10.1128/jb.00995-10
|View full text |Cite
|
Sign up to set email alerts
|

Instability ofackA(Acetate Kinase) Mutations and Their Effects on Acetyl Phosphate and ATP Amounts inStreptococcus pneumoniaeD39

Abstract: Acetyl phosphate (AcP) is a small-molecule metabolite that can act as a phosphoryl group donor for response regulators of two-component systems (TCSs). The serious human respiratory pathogen Streptococcus pneumoniae (pneumococcus) synthesizes AcP by the conventional pathway involving phosphotransacetylase and acetate kinase, encoded by pta and ackA, respectively. In addition, pneumococcus synthesizes copious amounts of AcP and hydrogen peroxide (H 2 O 2 ) by pyruvate oxidase, which is encoded by spxB. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 53 publications
9
81
0
Order By: Relevance
“…The strains MK127 and MK128, containing a deletion mutation in the capsule locus, were made by transforming the strains JWV500 and MK119, respectively, with a PCR product causing replacement of the gene cps2E (encoding a glucose phosphotransferase which initiates capsule synthesis) with a kanamycin resistance gene (M. G. Jørgensen and J.-W. Veening, unpublished data). This deletion is similar to a deletion that was described previously by RamosMontañez et al (29).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…The strains MK127 and MK128, containing a deletion mutation in the capsule locus, were made by transforming the strains JWV500 and MK119, respectively, with a PCR product causing replacement of the gene cps2E (encoding a glucose phosphotransferase which initiates capsule synthesis) with a kanamycin resistance gene (M. G. Jørgensen and J.-W. Veening, unpublished data). This deletion is similar to a deletion that was described previously by RamosMontañez et al (29).…”
Section: Methodssupporting
confidence: 60%
“…To do so, we introduced a capsule mutation in both the HlpA-GFP and HlpA-RFP reporter strains. The capsule mutation introduced was ⌬cps2E (here designated ⌬cps) which has been used in other studies (29,47) and has been shown to produce capsule-deficient cells. Next, we performed competition of bacterial adherence between HlpA-GFP (strain JWV500) and a ⌬cps strain expressing HlpA-RFP (⌬cps/ HlpA-RFP; MK128) or between HlpA-RFP (MK119) and a ⌬cps/ HlpA-GFP (MK127) strain and added them to a confluent A549 monolayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This observation directly links the acetylphosphate level in the cytosol to dormancy control. Thus, intracellular accumulation of acetyl-phosphate might disturb global signal transduction and has a toxic effect on the cells (62,63), whereas lack of acetyl-phosphate might result in reduced phosphorylation of response regulators and thereby in altered gene expression. The inability of the ⌬pta knockout strain to grow in the presence of acetate might therefore result from an intracellular increase in the acetyl-phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Strains containing antibiotic markers were constructed by transforming linear DNA amplicons synthesized by overlapping fusion PCR into competent pneumococcal cells as described previously (43,49,51,53). Primers synthesized for this study are listed in Table S2 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…The same patterns of transformation were observed in encapsulated strain D39 and derivatives, indicating that capsule did not play a role in the low rate of recovery of ⌬mreC, ⌬mreD, and ⌬mreCD mutants (see below and data not shown). The appearance of relatively low numbers of colonies of variable sizes after longer incubation is a hallmark of suppressor mutation accumulation (1,49).…”
Section: Vol 193 2011 Properties and Localization Of Pneumococcal Mmentioning
confidence: 99%